Sexual Objectification and Attitude towards Rape Victims: Mediating Role of Rape Myth Acceptance - Memoona Ashraf; Dr. Summaira Naz; Dr. Rabia Bahir; Dr. Humaira Bibi , (Dialogue Social Science Review (DSSR), 2025)
The current research aimed to explore the mediational effect of acceptance level of rape myth in the relationship of sexual objectification and attitudes towards rape victims. Additionally, the study sought to examine the influence of age, educational level and gender on study variables. 400 research participants having age range of 25-60 years (M=38.21, SD=13.31) were selected through convenient sampling strategy from five Khyber Pakhtunkhwa’s cities (Haripur, Abbottabad, Charsada, Mansehra and Mardan,) and two Azad Kashmir region’s cities (HatianBala and Muzaffrabad). The Attitude towards Rape Victims scale (Ward, 1988), Updated Illinois Rape Myth Acceptance Scale (McMahon & Farmer, 2011), and The Interpersonal Sexual Objectification Scale (Kozee et al., 2007) were administered for data collection. The findings revealed a positive association of attitudes towards rape victims with both sexual objectification and rape myth acceptance. Furthermore, the study demonstrated that rape myth acceptance played a significant mediating role in the relationship between sexual objectification and attitudes towards victims of rape. Moreover, the results indicated that educational level and age of victims did not yield significant differences, while gender showed a significant distinction. Specifically, females exhibited higher levels of sexual objectification, whereas males demonstrated higher tendency to accept rape myth and exhibit more negative attitudes for the victims of rape. In conclusion, this study emphasized the impact of rape myth acceptance as a mediating factor, altering the strength/degree of the association sexual objectification ha with attitudes towards the victims of rape.